Comparison of moss bag and native moss technique in monitoring airborne particulate and toxic elements - Nguyễn, Thị Minh Sang (2024)
Introduction: In Vietnam, the government has invested in monitoring stations in a few big cities like Hanoi and Ho Chi Minh City, which have transportation centers and industrial zones, to assess and predict levels of air pollution. However, the main disadvantage of installing monitoring stations is the cost of investment for operations, maintenance, and equipment. It is also time-consuming to collect and analyze the results. Therefore, it is generally not suitable for the country as a whole.